The Synergy of the Indonesian Islamic Calendar with the Local Wisdom of the 10 Muharram Tradition 1442 H/2020 M in the Central Market of Palakka (an Ethno-Cultural Analysis of the Purchase Decision of Bella Pitunrupa for Bugis Ethnicity) - Farida, Ida; Syamsuddin, S. (Golden Ratio of Social Science and Education, 2024)
The paper describes the synergy of the Indonesian Islamic calendar with the local wisdom of the 10 Muharram tradition in ethnic Bugis. Ethno-cultural issues associated with Bella Pitunrupa's staple purchasing decisions at the Palakka central market in Bone. The instrument of analysis is not just a scientific play on price fluctuations, supply and demand, market price competition hunting for blessings and related socio-economic ethno-culture, formal juridical, living philosophy of humanism and the urgency of the Islamic calendar in daily life itself. The ethno-cultural analysis of 10 Muharram on the decision to purchase Bella Pitunrupa staples for ethnic bugs in the central market of Bone Regency is very important to study to understand the synergy of the Indonesian Islamic calendar with the local wisdom of the 10 Muharram tradition. The type of verification qualitative research is the analysis of theory and field research through a casuistic normative approach. The data analysis method in this research is qualitative cross-science with ideal-normative deductive reasoning. The results showed that theoretically there is no harm in traders understanding and using the Indonesian Islamic calendar as an indicator of understanding price fluctuations in general ahead of 10 Muharram. After the data is collected and data checking or verification is held to test the validity of field data in the central market of Bone regency related to Bella Pitunrupa's staples. Analyzing the collected data and classifying the quality of primary and secondary data needed. The author makes conclusions and suggestions relating to the purchase decision of Bella Pitunrupa ethnic bugis in the central market of Bone district.